Combining Stress Exposure and Stress Generation: Does Neuroticism Alter the Dynamic Interplay of Stress, Depression, and Anxiety Following Job Loss?. Issue 4 (17th June 2016) - Howe, George W.; Cimporescu, Maria; Seltzer, Ryan; Neiderhiser, Jenae M.; Moreno, Francisco; Weihs, Karen
Abstract: Objective: Emerging models of stress point to a dynamic formulation where stressors and internalizing symptoms reciprocally influence each other. This study tested whether this dynamic interplay is the result of a general internalizing process underlying both depression and anxiety, and whether it varies with neuroticism. Method: A total of 426 adults (51% female; 47% White, 42% African American) were assessed five times over 6 months following loss of employment, using repeated measurements of stressors, depression, anxiety, and neuroticism. Results: Latent growth across 6 months and multilevel cross‐lagged regressions across 6 weeks supported the hypothesis that stressors and internalizing symptoms have reciprocal effects after job loss. Findings for unique variation in depression paralleled those for general internalizing, whereas few findings emerged for general or social anxiety after controlling for internalizing. Neuroticism strengthened the association of change in stressors with change in symptoms across 6 months. Those with high neuroticism showed less reduction in internalizing following reemployment and were less likely to be reemployed when starting with higher internalizing. Conclusions: The moderated reciprocal effects model helps account for onset, maintenance, and resolution of symptoms following job loss. We speculate that these findings may be due in part to differential emotion regulation and reductions in motivation.